Predicting the Ms temperature of lean alloyed ferritic–austenitic stainless steels - Sampo Uusikallio; Aarne Pohjonen; Pentti Kaikkonen; Oskari Haiko; Jukka Kömi (Journal of Materials Research and Technology)
A set of laboratory hot-rolled and thermally cycled 19–22 wt% Cr lean alloyed ferritic–austenitic stainless steels were studied with respect to calculated equilibrium austenite composition and experimental martensite start (Ms) temperature. Differences in Ms temperatures were achieved by altering alloying elements such as Mn, Ni, N and Cr. A new model predicting Ms temperature for lean alloyed ferritic–austenitic stainless steels was created. A link between the Ms temperature model of this study and the Ms temperature formula of the research of Finkler & Schirra was formed to create a connection between lean alloyed ferritic–austenitic stainless steel and martensitic stainless steel. The proposed model predicts Ms temperature for targeted stainless steels more precisely.